Pengaruh Bantuan Raskin, PDRB dan Belanja Daerah Terhadap Jumlah Penduduk Miskin di Kabupaten Se-Benua Enam - Salsabila, Sinta Nur; Yunani, Ahmad (PPJP ULM, 2023)
This research aims to know the effect of Raskin assistance, PDRB, and regional spending on the number of poor people in the Continent Six Regency and learn what factors dominate the Continent Six Regencies. Data collection techniques in this study use documentary techniques. The data used is secondary data with regression analysis techniques panel data. The results of this study suggest that Raskin, PDRB, and regional spending towards the number of poor people in the continent six regency and Raskin are the dominant factors that affect the number of people poor in the continent six regency.